FERMI LARGE AREA TELESCOPE OBSERVATIONS OF MARKARIAN 421: THE MISSING PIECE OF ITS SPECTRAL ENERGY DISTRIBUTION - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2011)
We report on the gamma-ray activity of the high-synchrotron-peaked BL Lacertae object Markarian 421 (Mrk 421) during the first 1.5 years of Fermi operation, from 2008 August 5 to 2010 March 12. We find that the Large Area Telescope (LAT) gamma-ray spectrum above 0.3 GeV can be well described by a power-law function with photon index Gamma = 1.78 +/- 0.02 and average photon flux F(>0.3 GeV) = (7.23 +/- 0.16) x 10(-8) ph cm(-2) s(-1). Over this time period, the Fermi-LAT spectrum above 0.3 GeV was evaluated on seven-day-long time intervals, showing significant variations in the photon flux (up to a factor similar to 3 from the minimum to the maximum flux) but mild spectral variations. The variability amplitude at X-ray frequencies measured by RXTE/ASM and Swift/BAT is substantially larger than that in gamma-rays measured by Fermi-LAT, and these two energy ranges are not significantly correlated. We also present the first results from the 4.5 month long multifrequency campaign on Mrk 421, which included the VLBA, Swift, RXTE, MAGIC, the F-GAMMA, GASP-WEBT, and other collaborations and instruments that provided excellent temporal and energy coverage of the source throughout the entire campaign (2009 January 19 to 2009 June 1). During this campaign, Mrk 421 showed a low activity at all wavebands. The extensive multi-instrument (radio to TeV) data set provides an unprecedented, complete look at the quiescent spectral energy distribution (SED) for this source. The broadband SED was reproduced with a leptonic (one-zone synchrotron self-Compton) and a hadronic model (synchrotron proton blazar). Both frameworks are able to describe the average SED reasonably well, implying comparable jet powers but very different characteristics for the blazar emission site.
CRIS-Team WoS Importer:2020-01-15